Eva A Novel by Carry Van Bruggen - Fenoulhet, Jane (UCL Press, 2019)
Eva, a 1927 novel by Dutch writer Carry van Bruggen, is an experiment in depicting a woman's life from girlhood to marriage, and beyond, to sexual freedom and independence. At the same time, the narrative expresses Eva's dawning sense of self and expanding subjectivity through a stream of consciousness told by a shifting narrator. Burdened all of her life by feelings of shame, at the end of the novel Eva overcomes this legacy of her upbringing and declares that it is 'bodily desire that makes love acceptable'.